Gas chromatography–mass spectrometry analysis of fatty acids in healthy and Aspergillus niger MH078571.1-infected Arabica coffee beans - Alabdalall, Amira H. (PLOS ONE, 2024)
The organic composition of Arabica coffee beans, particularly fatty acids, significantly influences their overall quality. After measuring its composition of fatty acids, it contained a high percentage of saturated fatty acids (SFA), including caprylic, lauric, myristic, palmitic, margaric, fat, and orchid. Moreover, the sample contained unsaturated fatty acids (USFA), namely palmitoleic acid (C16:1), oleic acid (C18:1), linoleic acid (C18:2), and alpha-linoleic acid (C18:3). Coffee beans are susceptible to infection by fungi during storage, the development of which has adverse effects on the beans. The present study aimed to examine the impact of Aspergillus niger MH078571.1 infection on the diversity and abundance of fatty acids in green Arabica coffee beans. The impact of Aspergillus niger on the consumption of fatty acids in Arabica coffee beans was assessed. The findings of the study indicate that the duration of storage had a significant impact on the levels of fatty acids, specifically miristic (C14:0), margaric (C17:0), and stearic (C18:0), which increased as the storage period and temperature increased. Conversely, the percentage of oleic acid decreased under these conditions. This trend was observed across different storage temperatures (0, 8, and 25°C) in untreated coffee beans affected by fungal activity.